Preparation of lead zirconate-lead nickel niobate ceramics by the reaction sintering process - Supamas Wirunchit (2018)
The perovskite structure of lead zirconate - lead nickel niobate ceramics, (1-x) PbZrO3-xPb(Ni1/3Nb2/3)O3 (PZ - PNN) at x between 0.00-0.50, has been prepared by the reaction-sintering process. The specimens were prepared directly from a mixture of their constituent oxide without any calcination step. The PZ - PNN ceramics could be obtained after 6 h sintering at 1,100-1,250°C. Crystal structure and phase transition of PZ-PNN were investigated by x-ray diffraction (XRD). XRD indicated that the structure of PZ-PNN ceramics is orthorhombic for a composition where x = 0.00, rhombohedral for compositions where x = 0.10 ≤ x ≤ 0.40 and pseudo-cubic for a composition where x = 0.50. The dielectric properties of the ceramics were measured as functions of both temperature and frequency. The results indicated that the transition temperature decreases with increasing PNN concentration. Furthermore, morphology and grain size evolution have been determined via a scanning electron microscope (SEM). Copyright © Taylor & Francis Group, LLC.